Ancient Concretes and Mortars of Selinous: Preliminary Results of the Projet CaF »Concretes as Floors« - Mège, Frédéric (Archäologischer Anzeiger, 2022)
The project CaF »Concretes as Floors« is an archaeological study of concrete floors carried out in Selinous and Megara Hyblaia in 2019–2020. Petrographic analyses and C-14 dating were at the heart of the investigations, meant to accurately determine the physicochemical properties of the floors and their prospective dates. One type of floor, the ›broken terracotta concrete/mortar‹ (BTC/BTM), most appreciated in the Antiquity, has been particularly investigated during the project because the technique’s developments are still unclear. This paper focuses on the results in Selinous. There, the analyses’ results have highlighted peculiar construction methods for the BTC/BTM floors, which could be explained by local technical traditions. They have also allowed refining their chronological framing, which turns out to be definitely wider than the sole Punic period of Selinous. Finally, their modes of utilisation in different living spaces, according to their physical properties, have been further evaluated.